2017
DOI: 10.14737/journal.aavs/2017/5.3.115.119
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Diseases-Possible Threat to Humans-Dog Interspecie Bond

Abstract: | Dog (Canine lupus familiaris) is one of the most neglected specie in the research institutes in Pakistan. Humans are at great risk of zoonotic diseases due to close association with dogs and humans-dog interspecies bond is at danger due to these diseases. The aim of the study was to determine the haemo-parasitic diseases of dogs, its effect on hematological profile and to correlate it with general health status of dogs. Total of 121 blood samples were collected from district Peshawar and Charsadda from publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Anticoagulant-added whole blood samples were processed through an automatic hematology analyzer (Urit Vet 2900) for the estimation of the total erythrocytic count, hemoglobin, hematocrit, total leucocytic count, and erythrocytic indices (Shah et al, 2017).…”
Section: Hematologymentioning
confidence: 99%
“…Anticoagulant-added whole blood samples were processed through an automatic hematology analyzer (Urit Vet 2900) for the estimation of the total erythrocytic count, hemoglobin, hematocrit, total leucocytic count, and erythrocytic indices (Shah et al, 2017).…”
Section: Hematologymentioning
confidence: 99%
“…Prevalence of intestinal parasites in ruminants is affected by various risk factors such as season, grazing habits, malnutrition and age of animals (Radostits et al, 1994;Adedipe et al, 2014). Development of parasites is mainly affected by hot weather due to which infestation of parasites (haemoparasites and intestinal parasites) is more common in hot and humid months of the year (Shah et al, 2017). The objective of the present study is to determine the prevalent GI parasites in study area and to determine the predisposing factors.…”
Section: Said Sajjadmentioning
confidence: 99%
“…have been observed in conventional diagnostic methods (e.g. blood smear examination) from dogs in Pakistan [21, 24–26]. Recent studies from Pakistan utilized molecular ( 18S rRNA gene amplification) approaches and reported a high prevalence (46% and 12%) of H. canis from farm and pet dogs, respectively [6, 27].…”
Section: Introductionmentioning
confidence: 99%